Sunburnt country : the history and future of climate change in Australia - Gergis, Joelle (Melbourne University Publishing, 2018)
What does climate change in Australia really look like?What was Australia's climate like before official weather records began? How do scientists use tree-rings, ice cores and tropical corals to retrace the past? What do Indigenous seasonal calendars reveal? And what do settler diary entries about rainfall, droughts, bushfires and snowfalls tell us about natural climate cycles?Sunburnt Country pieces together Australia's climate history for the first time. It uncovers a continent long vulnerable to climate extremes and variability. It gives an unparalleled perspective on how human activities have altered patterns that have been with us for millions of years, and what climate change looks like in our own backyard.